2021
DOI: 10.1126/sciadv.abe9444
|View full text |Cite
|
Sign up to set email alerts
|

On-demand biomanufacturing of protective conjugate vaccines

Abstract: Conjugate vaccines are among the most effective methods for preventing bacterial infections. However, existing manufacturing approaches limit access to conjugate vaccines due to centralized production and cold chain distribution requirements. To address these limitations, we developed a modular technology for in vitro conjugate vaccine expression (iVAX) in portable, freeze-dried lysates from detoxified, nonpathogenic Escherichia coli. Upon rehydration, iVAX reactions synthesize clinically relevant doses of con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 80 publications
(139 citation statements)
references
References 86 publications
3
128
0
Order By: Relevance
“…For the proof-of-concept studies performed herein, we selected the C. jejuni N-linked glycosylation system as a model because of the flexibility of CjPglB as a stand-alone, single-subunit OST 44 that has proven to be compatible with a diverse array of glycan donors and acceptor protein substrates including some with therapeutic potential. To date, CjPglB has been used to generate glycoproteins bearing bacterial 24,35,50 and smaller human-type glycans 24,[51][52][53][54] , and has enabled cell-free, one-pot systems for making N-and O-linked glycoproteins 24,55 as well as antibacterial conjugate vaccines 56 . While not directly demonstrated in this work, cell-free strategies such as the glycosylationon-a-chip platform described here could eventually provide access to glycoproteins that are modified with larger, complex-type N-glycans that mimic the structures commonly found on many human glycoprotein drugs such as monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…For the proof-of-concept studies performed herein, we selected the C. jejuni N-linked glycosylation system as a model because of the flexibility of CjPglB as a stand-alone, single-subunit OST 44 that has proven to be compatible with a diverse array of glycan donors and acceptor protein substrates including some with therapeutic potential. To date, CjPglB has been used to generate glycoproteins bearing bacterial 24,35,50 and smaller human-type glycans 24,[51][52][53][54] , and has enabled cell-free, one-pot systems for making N-and O-linked glycoproteins 24,55 as well as antibacterial conjugate vaccines 56 . While not directly demonstrated in this work, cell-free strategies such as the glycosylationon-a-chip platform described here could eventually provide access to glycoproteins that are modified with larger, complex-type N-glycans that mimic the structures commonly found on many human glycoprotein drugs such as monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…To produce CRM197-FtO-PS glycoconjugate, E. coli strain CLM24 was transformed with plasmid pTrc99S-spDsbA-CRM197 4xDQNAT encoding the CRM197 carrier protein modified at its C-terminus with four tandemly repeated DQNAT glycosylation motifs (81), plasmid pGAB2 encoding the FtO-PS biosynthesis pathway (58), and plasmid pMAF10-PglB encoding the Campylobacter jejuni oligosaccharyltransferase PglB for transfer of the FtO-PS (82). Overnight cultures were subcultured 1:100 into fresh LB containing appropriate antibiotics.…”
Section: Strainsmentioning
confidence: 99%
“…With a functional CRISPR-Cas12 diagnostic for Wolbachia detection in hand, we next wanted to assess the possibility of freeze-drying the system. Previous works have shown that cell-free systems, including CRISPR-based diagnostics, can be freeze-dried for increasing stability and portability 18,19 . Such features would be advantageous for preparation and delivery in the classroom setting.…”
Section: Characterization Of Freeze-dried Cas12 Diagnosticsmentioning
confidence: 99%